2020
DOI: 10.3389/fmolb.2020.00227
|View full text |Cite
|
Sign up to set email alerts
|

Determine the Potential Epitope Based Peptide Vaccine Against Novel SARS-CoV-2 Targeting Structural Proteins Using Immunoinformatics Approaches

Abstract: Coronaviruses (CoVs) belong to the Coronaviridae-family. The genus Betacoronaviruses, are enveloped positive strand RNA viruses with club-like spikes at the surface with a unique replication process and a large RNA genome (∼25 kb). CoVs are known as one of the major pathogenic viruses causing a variety of diseases in birds and mammals including humans (lethal respiratory dysfunctions). Recently, a new strain of coronavirus has been identified and named as SARS-CoV-2. A large number of COVID-19 (disease caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…This offers proof of the practical significance of immunoinformatics. Similarly, various studies reported MEV constructs for SARS-CoV-2 using one or multiple proteins [ 33 , 34 , 88 95 ]. But none of them used all anti-genic proteins of SARS-CoV-2 both structure and non-structure collectively to screen a pool of conserved/overlapping epitopes to design a comprehensive MEV construct.…”
Section: Discussionmentioning
confidence: 99%
“…This offers proof of the practical significance of immunoinformatics. Similarly, various studies reported MEV constructs for SARS-CoV-2 using one or multiple proteins [ 33 , 34 , 88 95 ]. But none of them used all anti-genic proteins of SARS-CoV-2 both structure and non-structure collectively to screen a pool of conserved/overlapping epitopes to design a comprehensive MEV construct.…”
Section: Discussionmentioning
confidence: 99%
“…Different CoVs have different host entry mechanisms, indicating that changes in the amino acid residues of the S protein determine whether the virus enters the host cell, and this property is used to design vaccines. [20][21][22] The main function of the N protein is to package the viral RNA into the helical ribonucleocapsid and interact with the other structural proteins during virion assembly. 23 The viral genome is filled with N proteins, which form a helical nucleocapsid protected by a lipid envelope.…”
Section: Introductionmentioning
confidence: 99%
“…The S protein binds to the host receptor through the receptor‐binding domain in the S1 subunit, and then, the S2 subunit is fused to the cell membrane. Different CoVs have different host entry mechanisms, indicating that changes in the amino acid residues of the S protein determine whether the virus enters the host cell, and this property is used to design vaccines 20–22 …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, peptides binding to the MHC class I and MHC class II were promising epitope based peptide vaccine candidates, when envelope protein was used as an immunogenic target [ 124 ]. A total of 10 epitopes based on the structural proteins designed by molecular docking analysis against MHC-I were identified which have the potential to be developed as peptide vaccine against SARS-CoV-2 [ 125 ]. A computational analysis identified the sequence KRSFIEDLLFNKV as particularly conserved in many coronaviruses, ranging from the common cold coronavirus to SARS-CoV-2.…”
Section: Classification Of Peptide Therapeutics For Covid-19 Based On the Mechanism Of Actionmentioning
confidence: 99%